Comparative analysis of economic efficiency of Polish and German listed companies - Artur Sajnog (Institute of Economic Research (IER), 2014)
The main subject of theoretical-empirical study presented in this paper is economic efficiency of companies listed on the Polish and German capital market . The discussed research problem was investigated in the form of a comparative analysis and realized in two parts. The discussion presented in the first part depicts mainly theoretical reflections on the essence and assessment measures of companies' economic efficiency. The second part presents the results of a comparative empirical research on economic efficiency of the companies listed on the Warsaw Stock Exchange and included in the WIG30 index as well as the companies listed on the Frankfurt Stock Exchange, which belong to the DAX index. The research period comprises years between 2004-2013. A comparative analysis of economic efficiency of the companies was conducted using a traditional ratio analysis and the nonparametric DEA method. The results of the empirical research confirm that German companies achieved significantly higher values of basic economic categories in the analysed decade, financial results in particular; however, their generated profits did not reflect in higher values of profitability ratios. Polish companies performed much better as they also showed higher efficiency from the DEA's point of view.
Keywords: G32; 330; efficiency; measure of efficiency; DEA; Polish and German joint-stock companies